Mathematics and informatics teacher education perspectives - Stankus, Eugenijus; Dagienė, Valentina (Lietuvos matematikos rinkinys, 2010)
The ongoing reform of Lithuanian higher education affected teacher education (or pre-service training) as well. Therefore it is important to review and update teacher training programs and to discuss them within community. This paper presents an overwiev, issues and perspectives of mathematics and informatics teacher training at the Vilnius University Faculty of Mathematics and Informatics.
Keywords: education reform; study programs; teacher training; mathematics teacher; informatics teacher; competencies